The volcanic ash plume near the Eyjafjallajökull on 1-2 May 2010 - Schumann, Ulrich; Baumann, Robert; Minikin, Andreas; Reitebuch, Oliver; Sailer, Thomas; Schlager, Hans; Voigt, Christiane; Weinzierl, Bernadett (2011)
This paper describes the analysis of airborne measurements and model simulations of the volcanic ash plume close to Iceland’s Eyjafjallajökull volcano in April/May 2010. In particular we quantify the plume properties for the period of 1 to 2 May, 2010, up to 450 km downstream the volcano. The measurements provide information on the plume width, upper height, mean depth, wind speed profile, attenuated Lidar backscatter profile, plume temperature, ash particle sizes, ash mass concentration, ash particle size distribution, humidity, O3, CO and SO2 mixing ratio, ash optical depth, volume flux, and mass flux. Here we report about analysis of the optical depth from the Lidar observations using the shadow method, and on comparisons of modeled and measured plume properties constraining the ash properties.